Multi‐Photon Absorption in Metal–Organic Frameworks. Issue 46 (24th October 2017) - Medishetty, Raghavender; Nemec, Lydia; Nalla, Venkatram; Henke, Sebastian; Samoć, Marek; Reuter, Karsten; Fischer, Roland A.
Abstract: Multi‐photon absorption (MPA) is among the most prominent nonlinear optical (NLO) effects and has applications, for example in telecommunications, defense, photonics, and bio‐medicines. Established MPA materials include dyes, quantum dots, organometallics and conjugated polymers, most often dispersed in solution. We demonstrate how metal–organic frameworks (MOFs), a novel NLO solid‐state materials class, can be designed for exceptionally strong MPA behavior. MOFs consisting of zirconium‐ and hafnium‐oxo‐clusters and featuring a chromophore linker based on the tetraphenylethene (TPE) molecule exhibit record high two‐photon absorption (2PA) cross‐section values, up to 3600 GM. The unique modular building‐block principle of MOFs allows enhancing and optimizing their MPA properties in a theory‐guided approach by combining tailored charge polarization, conformational strain, three‐dimensional arrangement, and alignment of the chromophore linkers in the crystal. Abstract : Nonlinear optical properties of metal–organic frameworks (MOFs) have been enhanced to record high multi‐photon absorption cross‐section values by following five design criteria, which are supported by theory.